1969
DOI: 10.1111/j.1476-5381.1969.tb09508.x
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode studies in the frog isolated spinal cord during depression by general anaesthetic agents

Abstract: . Extracellular and intracellular potentials have been recorded from the isolated spinal cord of the frog during depression of synaptic transmission by volatile and barbiturate general anaesthetic agents. . Volatile agents did not impair conduction in presynaptic terminals in concentrations which completely blocked synaptic transmission. . Methohexitone consistently impaired conduction in presynaptic terminals long before transmission through polysynaptic pathways was blocked. . Volatile agents depressed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The available evidence suggests that the barbiturates act mainly at synapses, suppressing excitatory synaptic transmission (1)(2)(3)(4)(5)(6)(7)(8) and usually either preserving or augmenting inhibitory synaptic transmission (6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The action of barbiturates on the spinal monosynaptic pathway has received the most rigorous analysis, and it has been shown that, in low doses, they reduce the amount of transmitter released from the primary afferents (4 The pH of the drug solutions was adjusted when necessary with NaOH or HCl.…”
mentioning
confidence: 99%
“…The available evidence suggests that the barbiturates act mainly at synapses, suppressing excitatory synaptic transmission (1)(2)(3)(4)(5)(6)(7)(8) and usually either preserving or augmenting inhibitory synaptic transmission (6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The action of barbiturates on the spinal monosynaptic pathway has received the most rigorous analysis, and it has been shown that, in low doses, they reduce the amount of transmitter released from the primary afferents (4 The pH of the drug solutions was adjusted when necessary with NaOH or HCl.…”
mentioning
confidence: 99%
“…Thus, with urethane and ethanol as well as other short chain alcohols, the synaptic transmission was not more sensitive than axonal conduction, clearly indicating rather marked differences in selectivity of action among this group of general depressants. (Some of the reports are: BROOKS and ECCLES, 1947;SHAPOVALOV, 1963;CRAWFORD and CURTIS, 1966;SOMJEN and GILL, 1963;SOMJEN, 1963;SOMJEN et aI., 1965;THESLEFF, 1956;CRAWFORD, 1970;WESTMORELAND et aI., 1971;RICHARDS, 1971RICHARDS, , 1972aRICHARDS, , b, 1973RICHARDS, , 1974RICHARDS et aI., 1975;NICOLL, 1972NICOLL, , 1974NICOLL, , 1975aRICHENS, 1969;THOMSON and TURKANIS, 1973;GALINDO, 1969GALINDO, , 1972DEJONG et aI., 1970;ADAMS et aI., 1970;ADAMS, 1974;BARKER, 1975;BARKER and GAINER, 1973;BARKER and NICOLL, 1973;RANSOM and BARKER, 1975;WEAKLY, 1969;SCHLOSSER, 1971;GAGE, 1965;GAGE et aI., 1975;QUILLIAM, 1959;ZORYCHTA, 1974;KLEE, 1976, 1977. ) …”
Section: Alterations In Synaptic Transmission: Excitatory Transmissiomentioning
confidence: 96%
“…ZORYCHTA'S data are consistent with an action of the anesthetics resulting in either an increased level of existing presynaptic inhibition or altering more directly the transmitter release mechanism. It is, however, very difficult to delimit the degree to which the variable depression of electrical excitability of the postsynaptic neuron is significant to transmission block (SOMJEN, 1967;ZORYCHTA, 1974;RICHENS, 1969;EIDELBERG and WOOLEY, 1970;SHAPOVALOV, 1963). NICOLL (1975a, b) has recently extended the understanding of anesthetics using the frog spinal cord preparation to demonstrate that barbiturates either mimic or potentiate the action of the transmitter from the interneuron whose axon terminates on the presynaptic ending.…”
Section: B) Presynaptic Sites Of Action To Reduce Transmitter Synthesmentioning
confidence: 96%